EFFECT INSTAGRAM ON PURCHASE INTENTION BY BRAND AWARENESS DURING PANDEMIC - Wina Sugiani Sugana; Theresia Gunawan (Jurnal Riset Bisnis dan Manajemen, 2022)
The purpose of this study was to determine the role of brand awareness that mediates the effect of social media Instagram on purchase intention. This research is quantitative in nature using the SEM (Structural Equation Model) method to test the effect of these three variables. The research respondents were 111 people who were followers of the Coffee Toffee Cafe Bandung Instagram account. Data was collected by distributing questionnaires via google form using convenience sampling technique. The results of this study indicate that brand awareness mediates the effect of social media Instagram on purchase intention significantly and positively at Cafe Coffee Toffee Bandung. Based on the results of this study, it is recommended that the Bandung Coffee Toffee Cafe continues to maintain and improve social media Instagram because it can increase brand awareness and purchase intention from its consumers.